Influence of Systemic Conditions on Periodontium- Exploring the Oral Systemic Connection: A Mini-Review - Mahendra, Jaideep; Mahendra, Little; M, Janani; Sharma, (Lt Col) Vivek (International Journal Of Drug Research And Dental Science, 2022)
Background: Understanding the etiology and pathophysiology of periodontal disease, due to its chronic infectio-inflammatory nature, demands acknowledging that these infections may affect processes elsewhere in the body. At the same time, acknowledging the interaction between oral diseases and some systemic conditions requires dentists and periodontists to direct their practice and knowledge not only to events strictly related to the oral cavity but also to systemic conditions and diseases that may change or interfere with established preventive and therapeutic approaches.Aim: The aim of this literature review is to explore and understand the interrelationship and the influence of systemic diseases on periodontium thereby raising health practitioners' attention to the importance of oral health care on overall well-being, and underlining the necessity for a broader connection between medical and dental training.Review results: This review paper discusses the underlying relationship and the etiopathology linking periodontal diseases and various systemic disorders.Conclusion: Periodontitis is a continual source of infection and has been identified as a risk factor for several cardiovascular, pulmonary, endocrine, musculoskeletal, and reproductive system disorders. Oral health has an influence on overall well-being, and if comprehensive health care is to be realized, oral health should not be viewed as a distinct, remote, and less essential area of health that is completely unconnected to longevity and its quality. Medical and dental experts have a propensity to approach patient treatment from a localised rather than a systemic perspective. Given the growing body of evidence on the significance of oral infections like periodontitis in a variety of systemic diseases, it has become imperative to do a literature review on the issue.